Uniform, independent bifunctionalization of a metal-organic framework material - Satterfield, Christopher S. (Kansas State University, 2018)
Molecular architecture involves the assembly of molecular building blocks to form supramolecular structures and the decoration of their interiors. The evolution and gathering of molecular building blocks into supramolecular constructs include examples such as co-crystals, micelles, nanoparticles, etc. These cases offer novel and advantageous pathways for research in supramolecular chemistry, however, a class of materials known as metal-organic frameworks (MOFs) materials has emerged as a prime candidate for molecular construction and interior design. MOFs are highly tunable materials because they can be synthesized from a wide range of metals cations and organic linkers. The organic linkers can also be functionalized after the MOF material has been synthesized through a process known as post-synthetic modification (PSM). These materials can be synthesized using two different organic linkers, resulting in a mixed-ligand MOF. If these ligands are modifiable and react independently, the resulting MOF structure will be orthogonally functionalized. Upon PSM we hypothesize that our porous, mixed-ligand MOF will contain homogenous bifunctionality as a blueprint for the construction of a uniformly orthogonally functionalized MOF. The synthesis of the first metal-organic framework, KSU-1, is the first of its kind to be developed at Kansas State University. PSM strategies used in this research show successful functionalization of each organic linker leading to uniform bifunctionality throughout our material. Characterization studies commonly used with MOFs verifies the synthesis and PSM of KSU-1.
Keywords: Metal-Organic Frameworks; Metal-Organic Frameworks